The Role of Public Relations Strategies in Strengthening Islamic Primary School Reputation - Deny Hadi Siswanto; Kintoko; Muhammad Yusuf Rambe (Contemporary Education and Community Engagement (CECE), 2026)
This study aims to examine in depth how public relations strategies at SD Muhammadiyah Blunyah are implemented in building image, fostering trust, and strengthening the school's reputation as an Islamic educational institution. This study uses a qualitative descriptive approach to examine the public relations strategies of SD Muhammadiyah Blunyah in building the school's image, trust, and reputation. Data were collected through in-depth interviews, participant observation, documentation, and literature studies, then analyzed thematically with source triangulation to ensure validity. The results of the study indicate that the school's public relations strategies include improving the quality of educational services, such as Tahfidz classes and bilingual programs, as well as being active in social media publications with an agenda-setting approach and dialogic communication. Involvement in community-based public relations-based social activities also strengthens the image and trust of the community. The positive image that is formed has an impact on increasing parental trust, which is influenced by direct experience, interpersonal communication, and institutional content. The school's reputation has also increased, as seen from the growth in the number of registrations and the involvement of alumni and the community. However, challenges such as limited human resources and less structured public evaluation still need to be overcome. Research confirms that human strategies that integrate Islamic values ​​and digital engagement are the key to successfully building a school's reputation and competitiveness in the modern era